ISIS Bagian dari Hubungan (Respon) Islam-Barat - Ahmad Sahide (ILMU USHULUDDIN, 2015)
Islamic State of Iraq and Syria (ISIS) is a new phenomenon, mainly after the Arab Spring event in the past 2011 the Western people, ISIS is the new phenomenon of the terrorism becoming the threat of the world. Indonesia, the majority Muslim state, can not be escaped from the threat of the terrorist threat. Indonesia participates to eradicate the terrorism in the world, mainly in Indonesia itself. This paper tries to see the issue of terrorism which deals with the history of the Islam and the West encounter. It can be said that terrorismm is the part (effect) of the relationship of the two civilizations. This paper concludes that, from the history, we need to learn from the West how to lead the civilization by institutionalization of doubt (science), not the institutionalization of terrorism.